Elaboração e caracterização de smoothies de açaí (Euterpe oleracea M.) e manga (Mangifera indica L.) adicionados de Lactobacillus acidophilus LA-3 - Luciano, Winnie Alencar (2018)
The study of the vegetal matrix as vehicle for the addition of lactic acid bacteria (LAB) aiming at the elaboration of new products with probiotic characteristics has intensified in recent years. These non-dairy foods with functional properties resulting from the addition of probiotics present an alternative to reach a wider range of consumers, including those with lactose intolerance, dyslipidemia and vegetarians. The aim of this work was to evaluate the survival of the probiotic culture Lactobacillus acidophilus LA-3 in açaí (AS) and mango (MS) based smoothies and the impact of the incorporation of this strain on the physicochemical and sensorial characteristics of the product during 28 days cooled storage at 4 °C. The survival ability of the test strain incorporated in the smoothies during exposure to simulated gastrointestinal tract conditions was further evaluated. L. acidophilus LA-3 maintained viability during the 28 days of storage in both smoothies, presenting counts of approximately 7.5 and 8.5 log CFU/g in MS and AS, respectively. As for the physical-chemical characteristics, no significant changes were observed in the control beverages (smoothies without the addition of L. acidophilus LA-3) during storage, whereas in AS and MS containing the strain there was a reduction of pH and total soluble solids, accompanied by an increase in titratable acidity. Smoothies containing L. acidophilus LA-3 presented lower content of glucose, fructose and maltose and higher amounts of lactic and succinic acid than the control smoothies. In the first 24 hours of storage, the profile of phenolic compounds was altered in AS and MS containing L. acidophilus LA-3 and the reduction or increase of phenolic and/or flavonoid acids varied in smoothies. No changes were detected in the phenolic profile of AS and MS without containing L. acidophilus LA-3. In sensory evaluation, smoothies were described as sweet tasting beverages and characteristic of fresh fruits, intense color and creamy texture. AS and MS containing L. acidophilus LA-3 differed from controls for acid taste and fermented flavor attributes. At the end of the in vitro digestion, L. acidophilus LA-3 presented counts ≥ 7.6 log CFU / mL in both smoothies assayed. The results demonstrate the feasibility of incorporation of L. acidophilus LA-03 into AS and MS, suggesting these products as an alternative matrix for the preparation of non-dairy probiotics products.